A high-strength fracturing proppant with ZBSO glass phase and its preparation method and application

By using water -based rock chips, ZNO, B2O3 and other additives, the ZBSO glass phase is generated to solve the problem of difficulty preparing high -quality fracture support agents at low fever sintering temperature, and achieve high strength and low crushing voltage pressure. The preparation of cracked support doses meets the needs of oil and gas mining.

CN116947460BActive Publication Date: 2025-01-28CHINA NAT PETROLEUM CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210416102.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-20
Publication Date
2025-01-28
Estimated Expiration
2042-04-20

AI Technical Summary

Technical Problem

It is difficult to obtain fracturing proppants that meet the quality requirements at a sintering temperature below 1400°C with water bedrock chips, and the sintering temperature above 1400°C leads to coarse grains and many pores, which cannot meet the crushing rate requirements.

Method used

The use of water -based rock chips and water -based rock chips B as the raw material, combined with ZNO and B2O3 as additives, to generate ZBSO glass phase through ball milling, granular, drying, and two -step thermal treatment method to prepare high -intensity discoling support agents Essence

Benefits of technology

A high -intensity fracture support agent with a crushing rate of less than 10 % at a lower sintering temperature is achieved, which meets the quality requirements, reduces energy consumption, and realizes the recycling of water -based rock chips.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116947460B_ABST
    Figure CN116947460B_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength fracturing proppant with a ZBSO glass phase, a preparation method and an application thereof. The high-strength fracturing proppant consists of water-based rock cuttings A, water-based rock cuttings B, ZnO and B2O3. The water-based rock cuttings are used as raw materials, ZnO and B2O3 are used as additives, and after reasonable mass ratio, the raw materials are evenly mixed by ball milling, and then water is added to granulate by a spraying method to form a green body. A glass phase ZBSO with a pinning effect is formed by heat treatment, which can limit the abnormal generation of ceramsite grains. The sintering temperature can be reduced by the ZBSO liquid phase sintering effect, which is beneficial to improving the mechanical properties of the material, and a fracturing proppant with a crushing rate of less than 10% is obtained, which meets the quality requirements, and can realize the recycling of water-based rock cuttings, which is beneficial to solving the problem of environmental pollution and is expected to be used in the field of oil and gas production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental protection and resource recycling, and particularly relates to a high-strength fracturing proppant with a ZBSO glass phase and a preparation method and application thereof. Background Art

[0002] Water-based cuttings are a type of solid waste generated during oil exploration and development. The main components are shale, bentonite, lubricants, chlorides, etc., and their chemical composition is mainly Al2O3 and SiO2. If water-based cuttings are not treated or treated improperly, they can easily cause environmental pollution and endanger human health. In recent years, as my country continues to pay attention to environmental issues, it is required that solid wastes be reduced, environmentally friendly and resource-based. Therefore, it is urgent to develop new ways to treat water-based cuttings harmlessly and as a resource.

[0003] Water-based rock cuttings contain Al2O3 and SiO2 in their chemical composition, which are the basic raw materials for producing corundum phase and mullite phase. Corundum phase and mullite phase can be used to obtain structural materials with superior performance through appropriate proportions. As my country's oil and gas demand has been increasing in recent years, hydraulic fracturing technology can meet the growing oil and gas demand. Fracturing proppant is a key material for the successful completion of hydraulic fracturing technology, and its usage is increasing year by year. The preparation of fracturing proppant using water-based rock cuttings as raw materials can not only meet the needs of the oil and gas production field, but also achieve the reduction, environmental protection and resource utilization of solid waste. However, it is difficult to obtain fracturing proppant that meets the quality requirements by using only water-based rock cuttings. The reason is that the sintering temperature of corundum phase and mullite phase is usually more than 1400℃, and it is difficult to obtain corundum phase and mullite phase at less than 1400℃ with only water-based rock cuttings, resulting in the performance of the obtained fracturing proppant failing to meet the quality requirements (the crushing rate is greater than 10%). If the sintering temperature exceeds 1400°C, the resulting fracturing proppant still cannot meet the quality requirements due to coarse grains and more pores, and the energy consumption is high. Therefore, the preparation of fracturing proppant from water-based rock cuttings alone faces the problem of sintering temperature. Summary of the invention

[0004] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a high-strength fracturing proppant with a ZBSO glass phase and a preparation method and application thereof, so as to solve the problem of sintering temperature faced by fracturing proppant prepared with only water-based rock cuttings, so that the crushing rate requirements cannot be met, and at the same time, the recycling of water-based rock cuttings can be achieved.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The invention discloses a high-strength fracturing proppant with a ZBSO glass phase, which comprises, by weight, 100 parts of water-based rock cuttings A, 10 parts of water-based rock cuttings B, 0-10 parts of ZnO and 0-10 parts of B2O3; the crushing rate of the fracturing proppant is less than 10%.

[0007] Preferably, the bulk density of the fracturing proppant is 1.53-1.71 g / cm 3 , apparent density is 2.68~3.01g / cm 3 .

[0008] Preferably, the particle size of the fracturing proppant is 200-500 nm.

[0009] Preferably, the components of the water-based rock cuttings A, in parts by mass, include 13.92 parts of Al2O3, 3.79 parts of Fe2O3, 0.58 parts of TiO2, 1.94 parts of K2O, 0.74 parts of Na2O, 18.38 parts of CaO, and 24.63 parts of MgO; the mass fractions of CaO and MgO are both greater than 10%.

[0010] Preferably, the components of the water-based rock cuttings B, by mass, include 17.43 parts of Al2O3, 50.97 parts of SiO2, 5.38 parts of Fe2O3, 0.77 parts of TiO2, 3.02 parts of K2O, 1.54 parts of Na2O, 2.99 parts of CaO, and 3.09 parts of MgO.

[0011] The present invention also discloses a method for preparing the high-strength fracturing proppant having a ZBSO glass phase, comprising the following steps:

[0012] Step 1, weighing water-based rock cuttings A, water-based rock cuttings B, ZnO and B2O3, mixing the raw materials uniformly through ball milling, granulating, drying, and making green bodies;

[0013] Step 2: heat-treating the green body to generate a ZBSO glass phase in situ to obtain a fracturing proppant.

[0014] Preferably, the mass ratio of water-based rock cuttings A, water-based rock cuttings B, ZnO and B2O3 is 100:10:(2-10):(2-10).

[0015] Preferably, in step 1, the drying temperature is 60 to 80° C., and the drying time is 12 to 24 hours.

[0016] Preferably, in step 1, the ball milling speed is 100 to 200 r / min.

[0017] Preferably, in step 2, the heat treatment is a two-step heat treatment method, in an air atmosphere, firstly heating to 1250°C at a rate of 1-2°C / min and sintering for 5 minutes, then cooling to 1200°C at a cooling rate of 5°C / min and keeping warm for 2 hours.

[0018] The invention also discloses the application of the high-strength fracturing proppant with ZBSO glass phase in hydraulic fracturing.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The invention discloses a high-strength fracturing proppant with a ZBSO glass phase, comprising water-based rock cuttings A, water-based rock cuttings B, ZnO and B2O3. The water-based rock cuttings A and B are used to obtain a corundum phase and a mullite phase, and the SiO2 in the water-based rock cuttings B is used to add ZnO and B2O3 to obtain the ZBSO glass phase, wherein the mullite phase has high hardness and toughness, which is the essential reason why the fracturing proppant has high strength; the corundum phase has high hardness and can improve the mechanical properties of the fracturing proppant; the ZBSO glass phase can reduce the sintering temperature and inhibit the growth of grains, thereby being beneficial to improving the mechanical properties of the material, and obtaining a fracturing proppant with a crushing rate of less than 10%, meeting the quality requirements.

[0021] Furthermore, the bulk density of the obtained fracturing proppant is 1.53-1.71 g / cm 3 , apparent density is 2.68~3.01g / cm 3 , the lower density helps to improve the sand carrying capacity of hydraulic fracturing, so that the fracturing proppant can be fully transported to the energy storage fractures, thereby improving the supporting effect and then increasing oil and gas production.

[0022] Furthermore, the particle size of the fracturing proppant is between 200-500nm, with relatively uniform refined grains. The finer the grains, the fewer defects in the material, and the higher the degree of grain slip along the grain boundaries, so that the material has higher mechanical properties, which can improve the mechanical properties of the fracturing proppant sample and reduce the breakage rate.

[0023] Furthermore, the water-based rock cuttings A contain CaO and MgO with a mass fraction greater than 10%, and the two can form a spinel phase with excellent mechanical properties during the sintering process, which helps to improve the performance of the fracturing proppant and reduce the crushing rate to less than 10%.

[0024] The present invention also discloses a preparation method of the above-mentioned fracturing proppant, which uses water-based rock cuttings as raw materials, ZnO and B2O3 as additives, and after reasonable mass ratio and heat treatment, generates ZBSO glass phase in situ to obtain a high-strength fracturing proppant, realizes the recycling of water-based rock cuttings, is beneficial to solving environmental pollution problems, and is expected to be used in the field of oil and gas extraction. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is the XRD diagram of the fracturing proppant obtained in Example 4 of the present invention;

[0026] Figure 2 This is a SEM image of the fracturing proppant obtained in Example 4 of the present invention; in the image, M represents the mullite phase, and the light-colored grains are the corundum phase;

[0027] Figure 3 1 is an EDS linear scan of the fracturing proppant obtained in Example 4 of the present invention; wherein (a) is an SEM image of the fracturing proppant, (b) is an EDS linear scan of the light dotted corundum phase in (a), and (c) is an EDS linear scan of the dark dotted mullite phase in (a). DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0029] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0030] The invention discloses a high-strength fracturing proppant with a ZBSO glass phase, a preparation method and an application thereof. The fracturing proppant comprises 100 parts of water-based rock cuttings A, 10 parts of water-based rock cuttings B, 2-10 parts of ZnO and 2-10 parts of B2O3. The compositions of the water-based rock cuttings A and B are shown in Table 1. The water-based rock cuttings A contain CaO and MgO with a mass fraction greater than 10%, and the two can form a spinel phase with excellent mechanical properties during the sintering process, which is helpful to improve the performance of the fracturing proppant and reduce the crushing rate to less than 10%.

[0031] The preparation method of the high-strength fracturing proppant with ZBSO glass phase provided by the present invention is as follows: water-based rock cuttings A and B are weighed according to the mass ratio, and considering that water-based rock cuttings B contains SiO2, it is only necessary to add ZnO and B2O3 in reasonable amounts, and the mixed raw materials are evenly mixed by ball milling, and then water is added to granulate by spraying to form a spherical green body with a diameter of 0.8 cm, and after heat treatment, it is cooled to room temperature with the furnace to obtain a high-strength fracturing proppant sample with ZBSO glass phase, and ZBSO is the abbreviation of zinc boron silicon oxide Zn-B2O3-SiO2. ZBSO is a glass phase that can form a nailing effect to limit the abnormal generation of ceramsite grains. The sintering temperature can be reduced by 100-200°C by using the ZBSO liquid phase sintering effect, which is beneficial to improving the mechanical properties of the material, obtaining a fracturing proppant that meets the quality requirements (the crushing rate is less than 10%), and then solving the problem of recycling water-based rock cuttings.

[0032] In the above preparation method, the mass ratio of the water-based rock cuttings A to the water-based rock cuttings B is 100:10.

[0033] In the above preparation method, the mass ratio of water-based rock cuttings A, water-based rock cuttings B, ZnO and B2O3 is 100:10:(2-10):(2-10).

[0034] In the above preparation method, the heat treatment is a two-step heat treatment method. In an air atmosphere, the temperature is first raised to 1250°C at a rate of 1-2°C / min and sintered for 5 minutes, then cooled to 1200°C at a cooling rate of 5°C / min and kept at this temperature for 2 hours, and then cooled to room temperature with the furnace.

[0035] Table 1 Composition of two water-based cuttings

[0036]

[0037]

[0038] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0039] Example 1

[0040] In this embodiment, water-based rock cuttings A and water-based rock cuttings B are used as raw materials, ZnO and B2O3 are used as additives, and the mass ratio of water-based rock cuttings A, water-based rock cuttings B, ZnO and B2O3 is 100:10:2:2. According to the mass ratio, 10 kg of water-based rock cuttings A, 1.0 kg of water-based rock cuttings B, 0.2 kg of ZnO and 0.2 kg of B2O3 are taken, and the mixture is evenly mixed in a ball mill at a speed of 200 r / min. The mixed powder is added into a granulator, granulated by adding water by spraying method, and dried at 80°C to obtain a 0.8 cm spherical green body. The green body was heat treated in a muffle furnace, and the heating and cooling programs were controlled. The temperature was first raised to 1250°C at a rate of 2°C / min and sintered for 5 minutes. Then the temperature was lowered to 1200°C at a rate of 5°C / min and kept at that temperature for 2 hours. The green body was cooled to room temperature in the furnace to obtain a fracturing proppant sample. The sample was numbered 2#, and its properties are shown in Table 2.

[0041] Example 2

[0042] The difference between this embodiment and embodiment 1 is that the dosage of ZnO and B2O3 is different, and the other processes are the same. Specifically, the mass ratio of water-based rock cuttings A, water-based rock cuttings B, ZnO and B2O3 is 100:10:4:4. According to the mass ratio, 10 kg of water-based rock cuttings A, 1.0 kg of water-based rock cuttings B, 0.4 kg of ZnO and 0.4 kg of B2O3 are taken. The obtained sample is numbered 3#, and its properties are shown in Table 2.

[0043] Example 3

[0044] The difference between this embodiment and embodiment 1 is that the dosage of ZnO and B2O3 is different, and the other processes are the same. Specifically, the mass ratio of water-based rock cuttings A, water-based rock cuttings B, ZnO and B2O3 is 100:10:6:6. According to the mass ratio, 10 kg of water-based rock cuttings A, 1.0 kg of water-based rock cuttings B, 0.6 kg of ZnO and 0.6 kg of B2O3 are taken. The obtained sample is numbered 4#, and its properties are shown in Table 2.

[0045] Example 4

[0046] The difference between this embodiment and embodiment 1 is that the amount of ZnO and B2O3 is different, and the other processes are the same. Specifically, the mass ratio of water-based rock cuttings A, water-based rock cuttings B, ZnO and B2O3 is 100:10:8:8. According to the mass ratio, 10 kg of water-based rock cuttings A, 1.0 kg of water-based rock cuttings B, 0.8 kg of ZnO and 0.8 kg of B2O3 are taken. The obtained sample is numbered 5#, and its properties are shown in Table 2. The phase composition, micromorphology and element distribution characterization results of the obtained samples are shown in Table 2. Figure 1-3 .

[0047] Figure 1The XRD test results of Example 4, the peak corresponding to the diamond mark is the mullite phase, the circular mark corresponds to the corundum phase, and the heart-shaped mark corresponds to the ZBSO glass phase. Among them, the mullite phase has high hardness and toughness, which is the essential reason why the proppant has high strength; the corundum phase has high hardness and can improve the mechanical properties of the proppant; ZBSO plays a role in lowering the sintering temperature and inhibiting grain growth. Furthermore, the principle of using ZBSO to limit the abnormal growth of fracturing proppant grains is that ZBSO is in liquid phase at 1250°C, can be distributed around the fracturing proppant grains, dissolve part of the grain surface, thereby forming a "core-shell" structure, and then limiting grain growth. Therefore, the reason why the fracturing proppant has a lower breakage rate can be concluded from the XRD test results.

[0048] Figure 2 The SEM characterization results are shown in Figure 1. The letter M corresponds to the micromorphology and grains of the mullite phase, and the letter M corresponds to the micromorphology and grains of the corundum phase. The SEM characterization results show that the fracturing proppant sample contains both mullite and corundum phases, which corresponds to the XRD test results. It can also be seen from the figure that the mullite and corundum phases are distributed more evenly, with a grain size between 200-500nm and relatively uniform refined grains. Studies have shown that the finer the grains, the fewer defects in the material, and the higher the degree of grain slip along the grain boundary, which makes the material have higher mechanical properties. This is the second reason for improving the mechanical properties of the proppant sample and reducing the crushing rate. In addition, the figure shows that the proppant sample has fewer pores (black tiny holes), that is, it has a higher density. The higher the density, the fewer defects in the material, which can improve the mechanical properties of the proppant sample, thereby achieving the purpose of reducing the crushing rate. This is the third reason for the low crushing rate of the proppant sample.

[0049] Figure 3 For Figure 2 Based on the SEM characterization, EDS line scans were performed on individual grains of mullite and corundum phases to illustrate that ZBSO is distributed around the grains. Figure 3 The light dashed lines in a and Figure 3As can be seen from b, the EDS line scan of a single grain of the corundum phase is completed along one side (start) to the corresponding side (end): from the boundary (0nm) to the center point (200nm), the Al and O element contents increase rapidly from low, and from the center point (200nm) to the other boundary (400nm), the Al and O element contents decrease rapidly from high. That is, the EDS line scan graph presents a parabolic shape opening downward, indicating that the grain is a corundum phase. From the boundary (0nm) to the center point (200nm), the Zn, B and Si element contents increase rapidly from low, and from the center point (200nm) to the other boundary (400nm), the Zn, B and Si element contents decrease rapidly from high. The EDS line scan graph presents a parabolic shape opening upward, indicating that ZBSO is distributed on the periphery of the corundum grains, forming a "core-shell" structure, which plays a role in assisting sintering, reducing the sintering temperature and limiting grain growth. From Figure 3 The dark dashed lines in a and Figure 3 c It can be seen that the EDS line scan of a single grain of mullite phase is completed along one side (start) to the corresponding side (end): from the boundary (0nm) to the center point (200nm), the content of Al, Si and O elements increases rapidly from low, and from the center point (200nm) to the other boundary (400nm), the content of Al, Si and O elements decreases rapidly from high. The EDS line scan graph presents a parabola shape with an opening downward, indicating that the grain is a mullite phase. From the boundary (0nm) to the center point (200nm), the content of Zn and B elements increases rapidly from low, and from the center point (200nm) to the other boundary (400nm), the content of Zn and B elements decreases rapidly from high. The EDS line scan graph presents a parabola shape with an opening upward, indicating that ZBSO is distributed on the periphery of the mullite grain, forming a "core-shell" structure, which plays a role in assisting sintering, reducing the sintering temperature and limiting grain growth.

[0050] Example 5

[0051] The difference between this embodiment and Embodiment 1 is that the dosage of ZnO and B2O3 is different, and the other processes are the same. Specifically, the mass ratio of water-based rock cuttings A, water-based rock cuttings B, ZnO and B2O3 is 100:10:10:10. According to the mass ratio, 10 kg of water-based rock cuttings A, 1.0 kg of water-based rock cuttings B, 1.0 kg of ZnO and 1.0 kg of B2O3 are taken. The obtained sample is numbered 6#, and its properties are shown in Table 2.

[0052] Comparative Example

[0053] The difference between this comparative example and Example 1 is that the dosage of ZnO and B2O3 is different, and the other processes are the same. Specifically, the mass ratio of water-based rock cuttings A, water-based rock cuttings B, ZnO and B2O3 is 100:10:0:0. According to the mass ratio, 10kg of water-based rock cuttings A, 1.0kg of water-based rock cuttings B, 0kg of ZnO and 0kg of B2O3 are taken. The obtained sample is numbered 1#, and its properties are shown in Table 2.

[0054] Table 2 Various indicators of samples

[0055]

[0056] It can be seen from the examples that different amounts of ZnO and B2O3 have a great influence on the performance of the samples. As the amounts of ZnO and B2O3 continue to increase, the amount of ZBSO generated increases accordingly; the crushing rate of the sample shows a trend of first decreasing and then increasing. This is because the increase in the amount of ZBSO will increase the density of the fracturing proppant and reduce the grain size, thereby reducing the crushing rate; as the amount of ZBSO further increases, there is too much ZBSO liquid phase, which is easy to accelerate the sintering rate, based on the dissolution-recrystallization mechanism, resulting in abnormal grain growth and increased pores, thereby increasing the crushing rate. Taking into account practical applications and comprehensive utilization, the ratio of sample 5# is taken as the optimal condition, that is, water-based rock cuttings A: water-based rock cuttings B: ZnO: B2O3 = 100:10:8:8. Therefore, in the high-strength fracturing proppant with a ZBSO glass phase prepared by the present invention, ZBSO can play a role in reducing the sintering temperature and inhibiting grain growth, thereby being beneficial to improving the mechanical properties of the material, obtaining a fracturing proppant with a breakage rate of less than 10%, meeting the quality requirements, and realizing the comprehensive utilization of water-based rock cuttings.

[0057] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A high-strength fracturing proppant having a ZBSO glass phase, characterized in that: The invention comprises, by weight, 100 parts of water-based rock cuttings A, 10 parts of water-based rock cuttings B, 2-10 parts of ZnO, and 2-10 parts of B2O3; wherein, the components of the water-based rock cuttings A, by weight, comprise 13.92 parts of Al2O3, 3.79 parts of Fe2O3, 0.58 parts of TiO2, 1.94 parts of K2O, 0.74 parts of Na2O, 18.38 parts of CaO, and 24.63 parts of MgO; the mass fractions of CaO and MgO are both greater than 10%; the components of the water-based rock cuttings B, by weight, comprise 17.43 parts of Al2O3, 50.97 parts of SiO2, 5.38 parts of Fe2O3, 0.77 parts of TiO2, 3.02 parts of K2O, 1.54 parts of Na2O, 2.99 parts of CaO, and 3.09 parts of MgO; and the crushing rate of the fracturing proppant is less than 10%.

2. The high-strength fracturing proppant having a ZBSO glass phase according to claim 1, characterized in that: The bulk density of the fracturing proppant is 1.53-1.71 g / cm 3 , apparent density is 2.68~3.01g / cm 3 .

3. The high-strength fracturing proppant having a ZBSO glass phase according to claim 1, characterized in that: The particle size of the fracturing proppant is 200-500 nm.

4. The method for preparing the high-strength fracturing proppant having a ZBSO glass phase according to claim 1, characterized in that: The following steps are involved: Step 1, weighing water-based rock cuttings A, water-based rock cuttings B, ZnO and B2O3 raw materials, mixing the raw materials uniformly through ball milling, granulating, drying, and making green bodies; Step 2: heat-treating the green body to generate a ZBSO glass phase in situ to obtain a high-strength fracturing proppant.

5. The method for preparing a high-strength proppant having a ZBSO glass phase according to claim 4, characterized in that: In step 1, the drying temperature is 60-80°C and the drying time is 12-24 h.

6. The method for preparing a high-strength proppant having a ZBSO glass phase according to claim 4, characterized in that: In step 1, the ball milling speed is 100-200 r / min.

7. The method for preparing a high-strength proppant having a ZBSO glass phase according to claim 4, characterized in that: In step 2, the heat treatment is a two-step heat treatment method. In an air atmosphere, the temperature is first raised to 1250 °C at a rate of 1-2 °C / min and sintered for 5 min, then cooled to 1200 °C at a rate of 5 °C / min and kept at this temperature for 2 h.

8. Use of the high-strength fracturing proppant having a ZBSO glass phase according to claim 1 in hydraulic fracturing.

Citation Information

Patent Citations

  • Porcelain calcined at low temperature, its manufacturing method and wiring board

    JP2002338341A